Edukasi self-management untuk meningkatkan self-care aktifitas fisik pada pasien diabetes melitus tipe 2 - Drissianti, Putri; Saputra, Fauzan; Risca, Amalia; Ismuhadi, Ismuhadi (JOURNAL of Public Health Concerns, 2026)
Background: Diabetes mellitus (DM) is a chronic disease characterized by high blood sugar levels resulting from insulin action, impaired insulin secretion, or both. It requires long-term treatment to reduce the risk of complications. DM cannot be cured, but blood sugar can be controlled through the four pillars of diabetes management: education, diet, exercise, and medication. Self-management is a crucial aspect in the management of type 2 diabetes mellitus (T2DM). However, patients with diabetes mellitus often fail to effectively manage themselves, resulting in macrovascular and microvascular complications. Purpose: To provide knowledge about self-care and physical activity based on self-management in DM patients. Method: This community service activity was carried out on December 15, 2025, at the Tanoh-Anou Village Community Health Center. Involving 51 people with DM as respondents. The target of this activity is the application of self-management for DM sufferers for self-care physical activity with a community-based approach. The intervention was carried out by delivering material related to the application of self-management in carrying out self-care physical activity, especially for DM sufferers, as well as an explanation of the benefits of physical activity for managing DM. Evaluation of the level of respondents' knowledge was measured using a questionnaire given before the educational activity (pre-test) and after the educational activity (post-test). Results: Obtained respondents with an age range of 36-77 years and the average age of respondents was 58.9 years and most of the respondents were in the range of 56-65 years as many as 21 people (41.2%). The majority were female as many as 42 people (82.4%), most had elementary/junior high school education status as many as 49 people (96.1%), and employment status was not as a farmer or fisherman as many as 42 people (82.4%). While the marital status was married as many as 40 people (78.5%) and the majority of the duration of suffering from DM was >3 years as many as 48 people (94.2%). There was an increase in the average score of respondents' knowledge level before educational activities (pre-test) from 16.2 points to 26.4 after educational activities (post-test). Conclusion: Self-management education activities covering diet management, physical activity, and foot care for people with diabetes mellitus significantly increased patients' knowledge of implementing physical activity self-care. This increased knowledge of self-management also positively contributed to psychological well-being and health motivation in diabetes patients. Suggestion: Similar educational activities are expected to be conducted routinely and sustainably to encourage healthy behavior changes and as an effort to prevent complications of diabetes mellitus early in the community. Keywords: Health education; Physical activity; Self-management; Type 2 diabetes mellitus Pendahuluan: Diabetes melitus (DM) merupakan penyakit kronis yang ditandai dengan kadar gula darah tinggi yang terjadi akibat kerja insulin, gangguan sekresi insulin, atau keduanya, dan memerlukan pengobatan jangka panjang untuk mengurangi risiko komplikasi. DM tidak dapat disembuhkan, namun gula darah dapat dikontrol melalui empat pilar pengelolaan diabetes, yaitu edukasi, pola makan, olahraga, dan pengobatan. Self-management merupakan salah satu aspek yang memegang peranan penting dalam penatalaksanaan diabetes melitus tipe 2 (DMT2). Namun dalam pelaksanaannya pasien dengan diabetes melitus tidak melakukan self-management dengan baik yang mengakibatkan terjadinya komplikasi makrovaskular dan mikrovaskular. Tujuan: Untuk memberikan pengetahuan tentang self-care aktifitas fisik berdasarkan self-management pada pasien DM. Metode: Kegiatan pengabdian kepada masyarakat ini dilaksanakan pada tanggal 15 Desember 2025 di Balai Puskesmas Desa Tanoh-Anou. Melibatkan 51 orang dengan DM untuk menjadi responden. Sasaran dalam kegiatan ini adalah penerapan self-management bagi penderita DM untuk self-care aktifitas fisik dengan pendekatan community-based. Intervensi dilakukan dengan menyampaikan materi terkait penerapan self-management dalam menjalankan self-care aktifitas fisik khususnya bagi penderita DM serta penjelasan tentang manfaat aktifitas fisik terhadap pengelolaan penyakit DM. Evaluasi tingkat pengetahuan responden diukur menggunakan kuesioner yang diberikan sebelum kegiatan edukasi (pre-test) dan sesudah kegiatan edukasi (post-test). Hasil: Mendapatkan responden dengan rentang usia 36-77 tahun dan rata-rata usia responden adalah 58.9 tahun dan sebagian besar usia responden dalam rentang 56-65 tahun sebanyak 21 orang (41.2%). Mayoritas berjenis kelamin perempuan sebanyak 42 orang (82.4%), sebagian besar memiliki status pendidikan SD/SMP sebanyak 49 orang (96.1%), dan status pekerjaan adalah bukan sebagai petani atau nelayan yaitu sebanyak 42 orang (82.4%). Sedangkan status pernikahan adalah menikah yaitu sebanyak 40 orang (78.5%) dan mayoritas lamanya menderita DM adalah >3 tahun yaitu sebanyak 48 orang (94.2%). Terdapat peningkatan rata-rata skor tingkat pengetahuan responden sebelum kegiatan edukasi (pre-test) dari 16.2 poin menjadi  26.4 sesudah kegiatan edukasi (post-test). Simpulan: Kegiatan pemberian edukasi self-management yang mencakup manajemen diet, aktivitas fisik, dan perawatan kaki untuk penderita diabetes melitus memberikan peningkatan pengetahuan yang cukup signifikan pada pasien dalam menerapkan self-care aktifitas fisik. Peningkatan pengetahuan tentang self-management juga memberikan kontribusi positif secara psikologis dan motivasi kesehatan pada pasien diabetes. Saran: Diharapkan kegiatan edukasi serupa untuk dilakukan secara rutin dan berkelanjutan agar mampu mendorong perubahan prilaku sehat dan sebagai upaya pencegahan komplikasi diabetes melitus sejak dini pada masyarakat.